Melatonin application alleviates adverse effects of low light on tobacco seedlings via enhancing antioxidant and carbohydrate metabolism - Xu, Wenzheng; Li, Peng; Pu, Tuanwei; liu, Qiaozhen; Han, Huige; Li, Yanping; Wu, Zhaohui (Frontiers in Plant Science, 2025)
There is relatively little knowledge about how melatonin helps tobacco withstand low light stress. To clarify this, a tobacco cultivar ZY100 was planted under light intensity of 150 μmol m-2 s-1 (low light) and 1000 μmol m-2 s-1 (control), and extra melatonin (200 μM) was applied to study the impacts of melatonin on tobacco seedlings under low light. Results showed that low light lowered plant height, stem thick, leaf number and shoot biomass, while melatonin alleviated these negative impacts of low light. Low light decreased net photosynthetic rate (AN), while melatonin application increased the AN of low light-affected tobacco by reducing stomatal and non-stomatal limitations. Low light promoted NtSOD, NtPOD and NtCAT (encoding superoxide dismutase, catalase and peroxidase, respectively) expressions, and ascorbate (AsA) and glutathione (GSH) contents in tobacco leaves, which was beneficial for antioxidation in theory, however, higher O2·- and H2O2 contents were still observed, damaging the AN. Melatonin application could further up-regulate NtSOD, NtPOD and NtCAT expressions and promote the AsA-GSH cycle by increasing ascorbate peroxidase and dehydroascorbate reductase activities in low light-affected tobacco leaves, lowering O2·- and H2O2 contents. Because low light decreased the AN, lower leaf sucrose and starch contents were measured in low light-affected tobacco. And the decreased sucrose in low light-affected tobacco leaves was attributed to the down-regulated NtSPS (encoding sucrose phosphate synthase) expression, and the up-regulated NtCWINV (encoding cell wall invertase) expression. The reduced starch in low light-affected tobacco leaves was associated to the down-regulated NtAGP (encoding ADP-glucose pyrophosphorylase) and NtGBSS (encoding granule-bound starch synthase) expressions, and the up-regulated expression of α-amylase. Melatonin application could up-regulate NtSPS expression to promote sucrose synthesis and down-regulate NtCWIN expression to inhibit sucrose hydrolysis in low light-affected tobacco leaves, increasing leaf sucrose content. Moreover, melatonin application up-regulated NtAGP and NtGBSS expressions to enhance the starch biosynthesis, finally resulting in increased starch content in low light-affected tobacco leaves. These results indicated that melatonin application can alleviate the adverse effects of low light on tobacco growth via regulating antioxidant and carbohydrate metabolism.